Synthesis, antimycobacterial, antifungal and photosynthesis-inhibiting activity of chlorinated N-phenylpyrazine-2-carboxamides - Dolezal, Martin; Zitko, Jan; Osicka, Zdenek; Kunes, Jiri; Vejsova, Marcela; Buchta, Vladimir; Dohnal, Jiri; Jampilek, Josef; Kralova, Katarina (Molecules (Basel, Switzerland), 2010)
A series of sixteen pyrazinamide analogues with the -CONH- linker connecting the pyrazine and benzene rings was synthesized by the condensation of chlorides of substituted pyrazinecarboxylic acids with ring-substituted (chlorine) anilines. The prepared compounds were characterized and evaluated for their antimycobacterial and antifungal activity, and for their ability to inhibit photosynthetic electron transport (PET). 6-Chloro-N-(4-chlorophenyl)pyrazine-2-carboxamide manifested the highest activity against Mycobacterium tuberculosis strain H37Rv (65% inhibition at 6.25 μg/mL). The highest antifungal effect against Trichophyton mentagrophytes, the most susceptible fungal strain tested, was found for 6-chloro-5-tert-butyl-N-(3,4-dichlorophenyl)pyrazine-2-carboxamide (MIC=62.5 μmol/L). 6-chloro-5-tert-butyl-N-(4-chlorophenyl)pyrazine-2-carboxamide showed the highest PET inhibition in spinach chloroplasts (Spinacia oleracea L.) chloroplasts (IC50=43.0 μmol/L). For all the compounds, the relationships between the lipophilicity and the chemical structure of the studied compounds as well as their structure-activity relationships are discussed.
Keywords: Antifungal Agents; Mycobacterium tuberculosis; Molecular Structure; Structure-Activity Relationship; Photosynthesis; Anti-Bacterial Agents; Chloroplasts; Hydrocarbons, Chlorinated; fotosyntéza; Spinacia oleracea; pyrazinamid; molekulární struktura; chloroplasty; chlorované uhlovodíky; vztahy mezi strukturou a aktivitou; antibakteriální látky; Trichophyton; antifungální látky; Pyrazinamide